(untitled) ("Conference on Universal Science Research 2023", 2023)
The issue of the humanistic elements in William Faulkner’s works is brought up in this article. Its primary goal is to provide a succinct overview of humanism’s significance in literature and to show that William Faulkner deserves a particular place alongside other humanists like Kierkegaard, Marcel, and Sartre. William Faulkner is one of the authors who has successfully incorporated humanistic concepts into their books, even though he is not sufficiently acknowledged as a humanist. This essay aims to demonstrate how Faulkner’s works not only take into account some key humanistic ideas but also pave the way for more humanistic discussions.